2021
DOI: 10.1016/j.heliyon.2021.e08262
|View full text |Cite
|
Sign up to set email alerts
|

Assessing volatile organic compound level in selected workplaces of Kathmandu Valley

Abstract: Volatile organic compounds (VOCs) are one of the major contributors to poor indoor air quality. Due to advancements in sensor technologies, continuous if not regular monitoring total VOC (TVOC) and or some specific VOC in potential high risk workplaces is possible even in resource limited settings. In this study, we implemented a portable VOC sensor to measure concentration of TVOC and formaldehyde (HCHO) in six types of potential high risk workplaces (n ¼ 56 sites) of Katmandu Valley. For comparison, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Many studies have been shown that long term airborne VOCs exposure leads to short-and long-term effects like allergy, nausea, headache, visual disorders, memory impairment, damage to kidney and liver, asthma, nose, and sore throat discomfort, and even cancer also (Yoon et .al, 2010;kharel et .al, 2021kharel et .al, , Ulker et al,2021. Several studies reported that the BTEX class is considered as highly carcinogenic, mutagenic, and genotoxic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been shown that long term airborne VOCs exposure leads to short-and long-term effects like allergy, nausea, headache, visual disorders, memory impairment, damage to kidney and liver, asthma, nose, and sore throat discomfort, and even cancer also (Yoon et .al, 2010;kharel et .al, 2021kharel et .al, , Ulker et al,2021. Several studies reported that the BTEX class is considered as highly carcinogenic, mutagenic, and genotoxic agents.…”
Section: Introductionmentioning
confidence: 99%